Compositional evolution of the NaZn13 structure motif in the systems La–Ni–Ga and Ce–Ni–Ga. Issue 37 (28th August 2018) - Prots, Yurii; Vasylechko, Leonid; Carrillo-Cabrera, Wilder; Drathen, Christina; Coduri, Mauro; Kaczorowski, Dariusz; Burkhardt, Ulrich; Grin, Yuri
Abstract : The sequence of morphotropic phase transformations has been found in the series LaNi13− x Ga x and CeNi13− x Ga x resulting in five varieties of the NaZn13 structure. Abstract : Phase relationship and structural behaviour in the substitutional series LaNi13− x Ga x and CeNi13− x Ga x have been studied by a combination of X-ray powder diffraction measurements, differential scanning calorimetry, electron diffraction tomography and metallographic analyses. The sequence of morphotropic phase transformations has been found in the series LaNi13− x Ga x resulting in five varieties of the NaZn13 structure: the cubic phase with aristotype structure at x = 2 (space group Fm 3̄ c, Pearson symbol cF 112), two tetragonal phases at x = 2.5–4.25 (space group I 4/ mcm, Pearson symbol tI 56-I) and 7–7.5 (space group I 4/ mcm, Pearson symbol tI 56-II), both with an atomic arrangement of the CeNi8.5 Si4.5 type and two orthorhombic phases at x = 4.5–5.75 (LaNi7 In6 structure type, space group Ibam, Pearson symbol oI 56) and x = 6.37–6.87 (a new derivative of the NaZn13, prototype structure, space group Fmmm, Pearson symbol oF 112). The related series CeNi13− x Ga x shows similar behaviour. The corresponding tI 56-I ↔ oI 56 ↔ oF 112 ↔ tI 56-II phases are formed at x = 4–4.25, 4.5–6, 6.37–6.87 and 7–7.37, respectively. In contrast to the lanthanum analogues, the phase with cubic symmetry was not found for this system. Complex twinned and multiple twinned (twinning of twins) domain structures which are revealed for the tetragonal and both orthorhombic phases clearly indicate temperature-induced polymorphic phase transitions during the formation of these phases. LaNi13− x Ga x samples show paramagnetic behavior, whereas the CeNi13− x Ga x series exhibits Curie–Weiss paramagnetism.